The impact of an outdoor play programme on the development of creative abilities in preschool children (aged 4–5 years) - Wissem, Alouane; Nacer, Touahria (The International tax journal, 2025)
This study examines the impact of an outdoor play programme on the development of creativity in pre-school children (aged 4–5 years), emphasising the importance of outdoor play in fostering cognitive, motor, and emotional skills during this critical developmental period. The researcher adopted a quasi-experimental design using an experimental method, implementing a directed play programme with a sample of kindergarten children divided into two groups: an experimental group who participated in the outdoor play programme over a specified period and a control group who continued with their usual classroom activities. The programme included a series of physical games and organised outdoor activities that focused on stimulating imagination, developing flexibility and fluency of thought, and encouraging exploration and creativity through free movement and interaction with elements of the outdoor environment. The level of creative ability was measured before and after implementation using appropriate tests for the preschool age group. These tests included indicators of fluency, flexibility, and originality of thought and performance. The results showed statistically significant differences in favour of the experimental group, indicating that outdoor play effectively contributes to the development of creative abilities in children.